Model attributes of Malaysian accounting educators in the 21st century / Corina Joseph and Josephine Avelind Noyem (Universiti Teknologi MARA, Sarawak, 2005)
The article focuses primarily on the role of accounting educators and the attributes that they should possess in educating future accounting graduates. Deppe et. al. (1991) provided direction for accounting educators by focusing on outcomes of the accounting educational process. They identified those competencies required to be successful as accountants and the points in the education process at which these competencies are being acquired. These competencies can be categorized into seven areas; communication skills, information development and e-commerce, decision making skills, knowledge of accounting, auditing and tax, knowledge of business and the environment, professionalism and leadership development. Meanwhile, the AICPA in 1999 developed a competency model to help students and Certified Public Accountants (CPAs) through their career and continuous learning plan which were categorized as personal attributes, leadership qualities, broad business perspective and functional specialty. Therefore, this paper aims at presenting a synthesis of the framework provided by Deppe et. al. and the AICPA.